ROCKWELL HARDNESS TESTING ON PURE NICKEL KOLIMATOR FOR BNCT APPLICATION - erasmus prakas ita (Indonesian Journal of Physics and Nuclear Applications, 2020)
In this study, Rockwell is used in material hardness examination. It caused by those characteristics. Those are, fast, away from human error, from this examination it can be known and compared the characteristics of nickel porosity before sentrifugal casting and after sentrifugal casting through hardness testing. To discover the element of nickel 99% porosity in Boron Neutron Capture Therapy (BNCT). the component used in BNCT in cylindrical shape and created in Sentrifugal casting method. The method which is used in this this project is hardness testing.